O impacto do imediatismo na formação e orientação da juventude: as possibilidades no desenvolvimento de lideranças frente ao imediatismo - Andrade, João Maicon Pereira (Universidade do Vale do Rio dos Sinos, 2025)
This article investigates the impact of immediacy on the formation and guidance of young leaders in an accelerated and hyperconnected cultural context. Based on Ignatian pedagogy and theorists such as Bauman, Lipovetsky, and ByungChul Han, the study analyzes integral formation and educational proposals that strengthen resilience, patience, and propose alternatives to the model of instant gratification. It also discusses the role of spirituality and human values in building conscious and committed leadership.
Keywords: Juventude; Imediatismo; Formação integral; Liderança; Espiritualidade; Youth; Immediacy; Integral formation; Leadership; Ignatian spirituality